KESIAPSIAGAAN MASYARAKAT: PARADIGMA BARU PENGELOLAAN BENCANA ALAM - Deny Hidayati (Jurnal Kependudukan Indonesia, 2008)
Indonesia lost hundreds of thousands of its people lives due to tsunami and earthquakes. A huge number of live lost reflects that the community preparedness was very low, mainly due to their lack of knowledge and awareness about these natural hazards and their negative impacts. The Indonesian government and its people used to be focused their activities on emergency response, rehabilitation and reconstruction phases. Community preparedness was not the priority in the management of disaster. The Aceh giant disaster has become a momentum to change the paradigm of disaster management by increasing community preparedness. As a natural disaster risk hotspot, most of Indonesian people are in vulnerable condition, leaving in high risk areas. Although having horrible experience of earthquakes and tsunamis, the community in high risk areas in the District of Padang Pariaman, Serang, Cilacap and Sikka, and the City of Bengkulu are still not enough prepared in anticipating the natural disasters. Public education and community preparedness therefore are crucially and urgently needed to reduce the disaster risks.Keyworc/: Preparedness, Community. Disaster; Natural